Use of Kurdish poem, melody and songs in funeral and condolence ceremonies (Raparin Journal of Humanities (RJH), 2024)
This investigation concentrates on the role and use of poem, melody and songs in the funeral ceremonies, through a critical scientific presentation and study based on historical aspects. By comparing and showing the positive and negative aspects of the art of singing in the condolence, through three main themes and several branches such as: The first content: Giving of the problem, importance and objectives of the research, identification of the scope of the research and definition of concepts. The second content: It is about presenting the content of the research and identifying the titles of the research which includes the following: Start with a historical look at poetic melody and texts in the condolence ceremonies (Shiwan, Shin and Lawanawa).  To determine the origin and extent of the phenomenon through the Kurdish nation. Then, through the analysis of the concepts and definitions of music, poem, Shin, Lawanawa and Shiwan. We have presented the structure and methods of performing these customs, traditions and cultures. After this, identified the forms of this ceremony by giving examples of (Cotal and Chamari). Through the manner in which actions are taken on funerals. At the end of this section, commenced to compare and importance these people. We have briefly discussed Shin and Lawanawa and its practice by Christians. In the third content, presented some of the results of our research, with some suggestions and recommendations for other collaborator and researchers in the field of art in general, song and music in particular, as a clarification for encouraging and conducting similar research.